Isolation, Characterization and Draft Genome Analysis of Bacteriophages Infecting Acidovorax citrulli - Gašić, Katarina; Obradović, Mina; Kuzmanović, Nemanja; Zlatković, Nevena; Ivanović, Milan; Ristić, Danijela; Obradović, Aleksa (Frontiers in Microbiology, 2022)
Bacterial fruit blotch and seedling blight, caused by Acidovorax citrulli, is one of the most destructive diseases of melon and watermelon in many countries. Pathogen-free seed and cultural practices are major pillars of the disease control. However, use of bacteriophages as natural biocontrol agents might also contribute to the disease management. Therefore, we isolated 12 bacteriophages specific to A. citrulli, from phyllosphere and rhizosphere of diseased watermelon plants. The phage strains were characterized based on their host range, plaque and virion morphology, thermal inactivation point, adsorption rate, one step growth curve, restriction fragment length polymorphism (RFLP), and genomic analysis. Transmission electron microscopy of three phage strains indicated that they belong to the order Caudovirales, family Siphoviridae. All phages lysed 30 out of 32 tested A. citrulli strains isolated in Serbia, and did not lyse other less related bacterial species. They produced clear plaques, 2 mm in diameter, on bacterial lawns of different A. citrulli strains after 24 h of incubation. The thermal inactivation point was 66 or 67°C. They were stable at pH 5–9, but were sensitive to chloroform and inactivated in either 5 or 10 min exposure to ultraviolet (UV) light. RFLP analysis using EcoRI, BsmI and BamHI enzymes did not show genetic differences among the tested phages. Adsorption rate and one step growth curve were determined for the Acidovorax phage ACF1. Draft genome sequence of the ACF1 phage was 59.377 bp in size, with guanine-cytosine (GC) content 64.5%, including 89 open reading frames. This phage shared a very high genomic identity with Acidovorax phage ACPWH, isolated in South Korea. Evaluation of systemic nature of ACF1 strain showed that it can be absorbed by roots and translocated to upper parts of watermelon plants where it survived up to 10 days.